Implementasi Augmented Reality Sebagai Media Pengenalan Hewan Dilindungi Berbasis Android Menggunakan Metode Image Tracking Vuforia - Nadya Humaira; Samirah Rahayu (SEMNASTERA (Seminar Nasional Teknologi dan Riset Terapan), 2020)
The development in the field of information technology is very rapid until now has penetrated on the concept of smartphone or smatrphone. One idea to optimize the usefulness of smartphones especially for early childhood is the application of Augmented Reality technology, which is a technology that combines virtual world objects with the real world in realtime. This gives the author the idea to create an interactive introductory medium using AR technology that can provide more perspective for the user, the advantage that this technology offers is without the absence of books but rather by using the world ball. The purpose of creating this app is to develop Augmented Reality-based apps on Android using vuforia AR library applied to help the introduction of animals to early childhood. The method used in this application is vuforia image tracking method, where image tracking is the main key of this technology, because the way the application is used is that the user points the camera at the marker found on the world ball then the protected animal 3D object will appear. The end result of this app is a flexible android mobile app that has a new appeal in the field of media recognition, designed with a more colorful and interactive concept that will provide a new learning atmosphere for early childhood with a minimum version of android 5.1 lollipop and the best distance camera on the marker between 30-60 CM with the best angle of 45°.